A PRÁTICA DA MÍDIA DIGITAL E SOCIAL NAS EMPRESAS DE RECREAÇÃO - Silva, Luis Carlos da (Revista Ilustração, 2025)
Abstract: Historically, the practice of sports activities between leisure and recreation is a divergent field full of growth and innovation. The objective of this work is to understand how the implementation of ESG can contribute to the growth of recreation companies, as a means of communication. In addition, how its performance can interfere with the environment and the well-being of people who do not practice leisure activities in recreational companies. Currently, companies, large and small, seek to relate the field with fun, excitement, the practice of health and well-being, seeking to relate a corporate field that can establish better development with programs that act in customer service. However, working with companies in the sports segment, feeds a sustainable way of bringing about an improvement in health, implementing satisfaction and motivation. Keywords: Recreational activities; Communication; innovation